2014
DOI: 10.1107/s2052520614002285
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin dimethylformamide 12.5 hydrate: a deeper insight into β-cyclodextrin crystal packing

Abstract: The structure of a 1:1 β-cyclodextrin-dimethylformamide hydrated complex has been determined from single-crystal X-ray diffraction data. A complete study of the structure is presented herein, including invariom refinement and interaction energy calculations. The structure has unit-cell parameters that are different from those of other β-cyclodextrin complexes crystallizing in the same space group, but exhibits the known herringbone packing type. A structural comparison of these complexes has been carried out w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…At the end of 2012, the group published a new crystal structure of the novel hydrate of -cyclodextrin crystallized at 0.65 GPa (Granero-García et al, 2012). At the beginning of 2014, they published the crystal structure of the first simple inclusion complex of -cyclodextrin and dimethylformamide (Granero-García & Fabbiani, 2014). The presentation at the microsymposium is a logical continuation of this work.…”
Section: High-pressure Crystallography Of Molecular Crystalsmentioning
confidence: 98%
“…At the end of 2012, the group published a new crystal structure of the novel hydrate of -cyclodextrin crystallized at 0.65 GPa (Granero-García et al, 2012). At the beginning of 2014, they published the crystal structure of the first simple inclusion complex of -cyclodextrin and dimethylformamide (Granero-García & Fabbiani, 2014). The presentation at the microsymposium is a logical continuation of this work.…”
Section: High-pressure Crystallography Of Molecular Crystalsmentioning
confidence: 98%
“…Also, it was found that on the basis of host–guest interactions, the CD is not only able to complex simple molecules (like the aromatic compounds [ 16 ]. or typical organic solvents [ 17 ]), but also linear polymers, as for example poly(ethylene glycol) (PEG) [ 18 ] or poly(acrylamide) [ 19 ] Interestingly, under appropriate pH conditions the CD is also capable to interact with typical hydrophilic linear macromolecules, i.e. the linear polyethylenimine (PEI) [ 20 ] or PEG [ 21 ] part of the PEG-PEI copolymer, which results in formation of polyrotaxane-like structures.…”
Section: Introductionmentioning
confidence: 99%